Hubungan Asupan Serat Dan Asupan Lemak Jenuh Dengan Kadar Kolesterol Darah Pada Lansia Di Posyandu Aisyiyah Kota Surakarta - HADHIROTUL RAMADHAN, SILFANISA; , Ahmad Farudin, SKM, M.Si; , dr. Listiana Darmawati, M.Si (2015)
Background : A person can be called elderly when he/she enters the age of 45 years. As the age increase, total cholesterol level is also higher then that of younger age. One of the efforts to control total cholesterol levels is with a proper nutritional therapy such as by increasing fiber intake and reducing intake of saturated fats in the diet. Objective : This research aimed to understand the relationship between intake of fiber and saturated fats and total cholesterol level in the eldery at Aisyiyah integrated health center of Surakarta. Research Method : This study was an observational research with cross sectional design. The subjects were selected through consecutive sampling technique, and obtained 42 research subjects with regard to the criteria for inclusion and exclution. Data collection on intake of fiber and saturated fats used the 24-hour recall method and total cholesterol level used electrode based biosensor. Analysis data used spearman's correlation tests. Result : The number of subjects who had less fiber intake was 97,60%, normal intake of saturated fats was 61,90%, and high total cholesterol level was 52,40%. Conclusion : Statistic tests showed there was no relationship between intake of fiber and total cholesterol level (p=0,65) and there was no relationship between intake of saturated fat and total cholesterol level (p=0,49)